The human thyroglobulin gene is over 300 kb long and contains introns of up to 64 kb. - Baas, F (1986)
Thyroglobulin (Tg), the precursor of thyroid hormones, is a 660.000 Da dimeric glycoprotein synthesized exclusively in the thyroid gland. We have cloned the human thyroglobulin gene from cosmid and phage libraries and constructed a complete restriction map. The gene encodes an 8.7 kb mRNA, covers at least 300 kb DNA and contains at least 37 exons separated by large introns of up to 64 kb. A striking difference in structure between the 5' and 3' part of the gene suggests that it is composed of two evolutionarily different regions. The first 30 kb DNA encode 3 kb of the mRNA, yielding an exon:intron ratio of 1:10, whereas the remaining 270 kb encodes 5.7 kb of the mRNA with an exon:intron ratio of 1:47. In thyroid cells, the Tg gene is not rearranged and nuclear RNA homologous with sequences internal to the 64 kb intron is present, suggesting that the Tg gene is transcribed as a 300 kb RNA.